WUJUD BUDAYA JAWA SEBAGAI UNSUR INKULTURASI INTERIOR GEREJA KATOLIK - Sari, Sriti Mayang (Dimensi Interior, 2007)
The Catholic Church adopts particular rules and meanings. Javanese culture also possesses rules, boundaries and meanings in building construction that includes space forming elements, facilities as well as other supportive elements. Inculturation of both these related cultures has to proceed in balance. Thus, comparisons must be drawn to be able to determine how far can a similar comprehension of meaning be achieved if inculturation of the Javanese culture and the Catholic church were to take place. Observation shows that not all the Javanese culture as an element of inculturation in the interior of the Catholic Church can be implemented physically because a similar comprehension of meaning would then be difficult and would contradict each other. Among the Javanese cultures that can be elements of inculturation in the interior of the Catholic church are in zoning, floor and ceiling elements, colour, the positioning of pews and furnitures for the leader. Abstract in Bahasa Indonesia : Gereja Katolik memiliki peraturan-peraturan dan makna-makna tertentu, Budaya Jawa pun memiliki aturan, batasan, serta makna tersendiri baik dalam tatanan bangunan yang meliputi elemen pembentuk ruang, fasilitas, maupun pendukung lainnya. Sedangkan dalam inkulturasi kedua budaya yang saling berhubungan ini harus berjalan seiring. Oleh karena itu, akan dibandingkan kedua budaya tersebut untuk mengetahui sejauh mana kesesuaian makna yang dapat dicapai apabila terjadi inkulturasi Budaya Jawa dengan Gereja Katolik. Dari hasil perbandingan tersebut diketahui bahwa wujud fisik Budaya Jawa sebagai unsur inkulturasi interior Gereja Katolik tidak semuanya dapat diterapkan karena tidak adanya kesesuaian makna dan hubungan timbal balik antara keduanya. Wujud Budaya Jawa yang dapat dijadikan unsur inkulturasi dalam interior Gereja Katolik antara lain zoning, elemen pembentuk ruang lantai dan plafon, warna, tata letak bangku umat dan perabot untuk pemimpin. Kata kunci: Interior Gereja Katolik, Liturgi, Inkulturasi Budaya, Budaya Jawa